Modulatable magnetically mediated thermoacoustic imaging with magnetic nanoparticles - Feng, Xiaohua (2015)
Modulatable magnetically mediated thermoacoustic imaging with magnetic nanoparticles is reported here. Under a pulsed radio frequency magnetic field, magnetic nanoparticles absorb energy strongly from the field and then emanate ultrasound signal thermoelastically. The energy absorption and, consequently, generated thermoacoustic signal strength depend sensitively on the magnetization state of magnetic nanoparticles, which can therefore be modulated effectively by a “bias” magnetic field. The magnetic modulation is demonstrated with a static magnet and modulated phantom imaging results are presented. This method offers an alternative modality for mapping magnetic nanoparticles and its unique modulation capability is demonstrated to be useful for contrast enhancement.